2013
DOI: 10.1074/jbc.m113.464974
|View full text |Cite
|
Sign up to set email alerts
|

TORC2 Is Required to Maintain Genome Stability during S Phase in Fission Yeast

Abstract: Background: TOR complex 2 (TORC2) is a conserved protein complex that regulates multiple aspects of cell survival and proliferation. Results: DNA metabolism and DNA damage response are impaired upon disruption of TORC2. Conclusion: TORC2 affects replication-associated damages, independent of checkpoint activation. Significance: TORC2 is required to maintain genome stability in fission yeast, a function that may be evolutionarily conserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 72 publications
2
44
0
Order By: Relevance
“…Disruption of TORC2 (⌬tor1, ⌬ste20, or ⌬sin1) results in pleiotrophic defects, including elongated cell morphology, deregulation of mitotic entrance, sensitivity to osmotic and oxidative stress, inability to enter sexual development or acquire stationary phase physiology, and a decrease in amino acid uptake (5-7, 9 -11). Recently, we have showed that TORC2 is required under DNA replication stress and for maintenance of telomere length and gene silencing (12). Interestingly, a role for TORC2 in maintenance of genome stability has also been reported in Saccharomyces cerevisiae (13), suggesting that the role of TORC2 in tolerance to DNA damage and genome integrity is conserved in evolution.…”
Section: Target Of Rapamycin (Tor)mentioning
confidence: 99%
See 2 more Smart Citations
“…Disruption of TORC2 (⌬tor1, ⌬ste20, or ⌬sin1) results in pleiotrophic defects, including elongated cell morphology, deregulation of mitotic entrance, sensitivity to osmotic and oxidative stress, inability to enter sexual development or acquire stationary phase physiology, and a decrease in amino acid uptake (5-7, 9 -11). Recently, we have showed that TORC2 is required under DNA replication stress and for maintenance of telomere length and gene silencing (12). Interestingly, a role for TORC2 in maintenance of genome stability has also been reported in Saccharomyces cerevisiae (13), suggesting that the role of TORC2 in tolerance to DNA damage and genome integrity is conserved in evolution.…”
Section: Target Of Rapamycin (Tor)mentioning
confidence: 99%
“…Consistent with our findings showing a rapid and translation-independent response of TORC2-Gad8 to glucose, the stimulating effect of the cAMP/ PKA pathway on TORC2-Gad8 was independent of the Pka1-regulated transcription factor Rst2. We have recently identified a role for TORC2-Gad8 in survival under DNA-damaging conditions, in particular those occurring during DNA replication (6,12). A screen for CPT-sensitive mutant cells has recently identified mutations in the cAMP/PKA pathway as sensitive to this drug (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon glucose withdrawal or shift from glucose to a less favorable carbon source such as glycerol, there is a reduction of TORC2-dependent phosphorylation of Gad8 at serine 546 (equivalent to serine 473 in AKT) and concomitant reduced Gad8 kinase activity (17, 18). Thus, S. pombe TORC1 and TORC2 play essential roles in regulating growth by responding to two distinct key nutritional cues.As mentioned above, our functional analysis of cells lacking TORC2 or Gad8 indicated a role for TORC2-Gad8 in the survival under DNA damage and replication stresses (10,11 …”
mentioning
confidence: 94%
“…In fission yeast, TORC2 is required for recovery from DNA replicative arrest (7) and maintenance of genome stability after S-phase-specific DNA damage (8). In budding yeast, TORC2 is required for maintenance of genome stability after double-stranded DNA (dsDNA) damage (9).…”
mentioning
confidence: 99%